2014
DOI: 10.1037/xap0000028
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subtle misinformation in news headlines.

Abstract: Information presented in news articles can be misleading without being blatantly false. Experiment 1 examined the effects of misleading headlines that emphasize secondary content rather than the article's primary gist. We investigated how headlines affect readers' processing of factual news articles and opinion pieces, using both direct memory measures and more indirect reasoning measures. Experiment 2 examined an even more subtle type of misdirection. We presented articles featuring a facial image of one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
153
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 73 publications
(129 reference statements)
4
153
1
10
Order By: Relevance
“…Headlines are still the primary communication method for news articles. Headlines' features such as their compact and clear nature make an immediate impression on readers and the results of the aforementioned research offer evidence that headlines affect the overall processing of information about an article (Ecker et al, 2014). All the above are associated with the text and consequently, may explain to an extent the finding that text was the most salient factor.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Headlines are still the primary communication method for news articles. Headlines' features such as their compact and clear nature make an immediate impression on readers and the results of the aforementioned research offer evidence that headlines affect the overall processing of information about an article (Ecker et al, 2014). All the above are associated with the text and consequently, may explain to an extent the finding that text was the most salient factor.…”
Section: Discussionmentioning
confidence: 74%
“…In the same vein, feedback to article may depend on the appeal of the article (Bastos, 2014). A recent study by psychologists found that misleading headlines have a significant effect on readers' memory for news articles as well as their inferential reasoning (Ecker et al, 2014). Headlines are still the primary communication method for news articles.…”
Section: Discussionmentioning
confidence: 99%
“…As Ecker et al (2014) highlight, this headline misleads the reader by overstating the claim made later in the article. First, omitting 'environmental' from the headline radically generalises the claim: a leading environmental cause may not be the leading cause, above all other causes.…”
Section: Kurt Straif Of Iarc [Emphasis Added]mentioning
confidence: 99%
“…although air pollution increases the risk of developing lung cancer by a small amount, other things have a much bigger effect on our risk, particularly smoking"), these nuances are lost in the headline. This seems particularly dangerous in the light of experimental work into reader behaviour: Ecker et al (2014) show that even after reading the article in full, a reader is likely to be left with their initial impression gained from the headline; and Gabielkov et al (2016) found that c.60% of shared URLs on Twitter are not clicked on before sharing, suggesting that in many cases only headlines are read. Automatic detection of these misleading cases could therefore directly impact the spread of misinformation.…”
Section: Kurt Straif Of Iarc [Emphasis Added]mentioning
confidence: 99%
See 1 more Smart Citation